AUTOMATIC TRAFFIC LIGHT SETTING SYSTEM USING PLC, CASE STUDY: FIVE MAIN INTERSECTIONS OF SOUTH TAMBUN - Yosua Julianto Perdamaian Sitompul; Antonius Doddy Tyas Prasetyo (Universitas Tarumanagara, 2026)
Traffic congestion and road user safety risks are major problems that frequently occur at intersections, especially during peak hours. Therefore, a more efficient, intelligent, and flexible control system is needed to optimize vehicle flow regulation at each intersection. One of the solutions that can be implemented is a programmable logic controller (PLC) based automatic traffic light setting system. This technology allows for automatic and precise timing of traffic signals, according to the pre-programmed sequence and duration based on the desired traffic conditions. This study aims to design, simulate, and analyze PLC-based automatic traffic light setting systems at a main five-leg intersection (Simpang Lima) in South Tambun District, Bekasi Regency. The system is designed to be able to adjust the red, yellow, and green flashes alternately according to the specified logical order and time. The use of PLCs in this system provides advantages in terms of reliability, ease of programming, and the ability to perform accurate automatic controls. The method carried out in this study is to simulate PLC, with system design carried out through the creation of a block diagram function that represents the working logic of each lamp at the five legs of the intersection. Kemacetan lalu lintas dan risiko keselamatan pengguna jalan merupakan permasalahan utama yang sering terjadi di persimpangan, terutama pada jam sibuk. Oleh karena itu, diperlukan sistem pengendalian yang lebih efisien, cerdas, dan fleksibel untuk mengoptimalkan pengaturan arus kendaraan di setiap simpang. Salah satu solusi yang dapat diterapkan adalah sistem pengaturan lampu lalu lintas otomatis berbasis programmable logic controller (PLC). Teknologi ini memungkinkan pengaturan waktu sinyal lalu lintas secara otomatis dan presisi, sesuai dengan urutan dan durasi yang telah diprogram berdasarkan kondisi lalu lintas yang diinginkan. Penelitian ini bertujuan untuk merancang, mensimulasikan, dan menganalisis sistem pengaturan lampu lalu lintas otomatis berbasis PLC pada persimpangan lima lengan (Simpang Lima) utama di Kecamatan Tambun Selatan, Kabupaten Bekasi. Sistem ini dirancang agar mampu mengatur nyala lampu merah, kuning, dan hijau secara bergantian sesuai urutan logika dan waktu yang ditentukan. Penggunaan PLC dalam sistem ini memberikan keunggulan dalam hal keandalan, kemudahan pemrograman, dan kemampuan Metode yang dilakukan dalam penelitian ini adalah dengan melakukan simulasi PLC, dengan perancangan sistem yang dilakukan melalui pembuatan function blok diagram yang merepresentasikan logika kerja dari setiap lampu pada lima lengan jalan persimpangan